Odpowiedzi

2010-01-09T17:39:42+01:00
A)35-(-6)=35+6=41
b)2/5 / (-8/5) - 4 2/3 × (-3/10) = 2/5 * (-5/8) - 14/3 × (-3/10) = (-1/4) - (-14/10) = (-1/4) + 7/5 = -0,25 + 1,4 = 1,15
c)(-10/3) * (-21/4) + (-12) * 3/4 = 35/2 + (-9) = 17,5 - 9 = 8,5

Pozdrawiam:)
2010-01-09T18:29:01+01:00
A) -5 × (-7) - (2-8) = 35 - (-6) = 41
b)⅖ ÷ (-1⅗) - 4²/₃ × (-³/₁₀) = 2/5 x 5/8 - 14/3 x (-3/10) =
= 1/4- ( - 42/30 ) = 1/4 + 42/30 = 1/4 + 1 12/30 = 15/60 + 84/60 = 99/60 = 1 39/60 = 1 13/20
c) (-3⅓) × (-5¼) + (-12) × ¾ = (-10/3) x ( - 21/4) + (- 36/4) = 8 i 1/2